Freshwater aquatic biomes - Roth, Richard A., 1950- (Greenwood guides to biomes of the world., 2009)
"Covers the freshwater biomes that exist in wetlands, ponds and lakes, and rivers and streams, examining all aspects that define these biomes: vegetation, geographical distribution, challenges posed by the environment, adaptation of the plants and animals to the environment, and conservation efforts"--Publisher's description.